Participatory Communication in Children Empowerment Program in Yogyakarta: The Case of Sekolah Gunung Merapi and Komunitas Jendela Jogja - Mutia Dewi; Muhammad Reza Fahlevy (Department of Communications, Universitas Islam Indonesia, 2019)
Using qualitative approach, this study aims to analyse the participatory communication in the children empowerment programs held by Sekolah Gunung Merapi and Komunitas Jendela Jogja, as well as its supporting and undermining factors. The data of this study were collected through in-depth interviews, semi-participant observations, and document collections. Six informants were involved in this study, which were purposively selected as they are activists of the two research communities. As a result, the study shows that participation in children empowerment programs in Yogyakarta appears at four processes: decision-making, activities implementation, monitoring and evaluation and outcome utility. In each process, they mostly use the concept of dialogue and carnival participation. In terms of participation level, the children empowerment programs held by Sekolah Gunung Merapi and Komunitas Jendela Jogja are both in partnership level with roles as accelerator, mediator, educator, expert and social planner. The supporting factors in the children empowerment programs include supports and facilities while the undermining factors are the lacks of number and teaching skill from volunteer’s side and troubles from student’s side.Keywords: Children empowerment program; participation; participatory communication; Sekolah Gunung Merapi; Komunitas Jendela Jogja.